2010
DOI: 10.1021/om100233y
|View full text |Cite
|
Sign up to set email alerts
|

The Reactivity of Phosphagermaallene Mes*P═C═Ge(t-Bu)Tip toward Aldehydes and Ketones: an Experimental and Theoretical Study

Abstract: Phosphagermaallene Mes*PCGe(t-Bu)Tip 1 (Tip = 2,4,6-triisopropylphenyl, Mes* = 2,4,6-tri-tert-butylphenyl) has been obtained by an improved synthesis in relation to the previously reported preparation starting from t-BuGeCl3. Very short GeC (1.761(2) Å) and PC (1.625(2) Å) double bond lengths, trigonal planar geometry around the Ge atom, and GeCP bond angle of 166.57° are indicative of an heteroallenic structure for 1. Its reactions with crotonaldehyde and cinnamaldehyde lead to 1-oxa-2-germacyclobutanes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…The energy profiles for the [2+2] and [3+2] cycloaddition reactions have been investigated on the parent compound H 2 Ge=C=PH 1 H to reach reasonable computation times and on the more sterically hindered compound 1 H' Me 2 Ge=C=PAr (methyl groups on the germanium atom and 2,6-dimethylphenyl on the phosphorus atom) to gain more information on the effect of the steric hindrance. In previous works [9,12] we have shown that 1 H correctly modeled the general properties (geometry, shape, and order of the main MOs) of the real compound TipA C H T U N G T R E N N U N G (tBu)Ge= C=PMes*.…”
Section: Wwwchemeurjorgmentioning
confidence: 80%
See 4 more Smart Citations
“…The energy profiles for the [2+2] and [3+2] cycloaddition reactions have been investigated on the parent compound H 2 Ge=C=PH 1 H to reach reasonable computation times and on the more sterically hindered compound 1 H' Me 2 Ge=C=PAr (methyl groups on the germanium atom and 2,6-dimethylphenyl on the phosphorus atom) to gain more information on the effect of the steric hindrance. In previous works [9,12] we have shown that 1 H correctly modeled the general properties (geometry, shape, and order of the main MOs) of the real compound TipA C H T U N G T R E N N U N G (tBu)Ge= C=PMes*.…”
Section: Wwwchemeurjorgmentioning
confidence: 80%
“…CÀH insertion with acetonitrile [11] and ene-reactions with compounds that present a slightly acidic hydrogen (acetophenone, [7] methyl vinyl ketone [9] ) have also been observed. But the phosphagermaallene 1 also behaves as a 1,3-dipole by reacting with acetylene dicarboxylate [12] and benzonitrile [11] through the entire Ge=C=P unit (Scheme 1).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations